Interaction and participation of the work teams and their role in improving the efficiency of the outputs of agricultural research centers in the General Authority for Scientific Agricultural Research A field study on the Scientific Agricultural Research - عمار علي أحمد; علي ميا; نضال عيسى (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The aim of this research is to determine the role of interaction and participation of the work teams in improving the efficiency of the outputs of the Scientific Agricultural Research Center in Tartous, by examining the dimensions of the efficiency of the outputs (knowledge, skills, good behavior), and their relationship to the interaction and participation of the work teams in the Scientific Agricultural Research Center in Tartous. To achieve the objectives of the study, a questionnaire was distributed to the workers at the aforementioned center. The researcher relied on the descriptive approach to conduct the research. The variables were measured through their dimensions. The researcher used the statistical method by designing a questionnaire to collect primary data from the research sample’s vocabulary in order to use it to test hypotheses. Then The researcher transcribed the questionnaire into a database that was analyzed using the SPSS program, version 20. Among the most important results of the research: The results of hypothesis testing indicate the existence of a strong positive relationship with high statistical significance between the variables of output efficiency (knowledge, skills, good behavior) and the interaction and participation of the work teams at the Scientific Agricultural Research Center in Tartous.